2017
DOI: 10.2463/mrms.tn.2015-0145
|View full text |Cite
|
Sign up to set email alerts
|

Pixel-by-Pixel Arterial Spin Labeling Blood Flow Pattern Variation Analysis for Discrimination of Rheumatoid Synovitis: A Pilot Study

Abstract: We examined the capability of a gray-scale arterial spin labeling blood flow pattern variation (BFPV) map with two different post labeling delay (PLD) times to discriminate pannus in patients with rheumatoid arthritis (RA) at 3T. There was a statistically significant difference in the BFPV values between artery, pannus, and surrounding tissue. Furthermore, the color-coded BFPV map was able to accurately distinguish pannus from other tissues. These results suggest this approach may be capable of identifying pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…IVIM simultaneously permits quantification of perfusion as well as diffusion using a single imaging scan . The perfusion information is useful for the assessment of inflamed synovitis in RA because an increased number/area of capillaries is observed in the inflamed synovial membrane as compared with the normal synovial membrane . As for differentiating synovitis from joint effusion using perfusion information, Hilbert et al indicated that the IVIM parameter f value facilitated visual differentiation in the knee joint of children with juvenile idiopathic arthritis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IVIM simultaneously permits quantification of perfusion as well as diffusion using a single imaging scan . The perfusion information is useful for the assessment of inflamed synovitis in RA because an increased number/area of capillaries is observed in the inflamed synovial membrane as compared with the normal synovial membrane . As for differentiating synovitis from joint effusion using perfusion information, Hilbert et al indicated that the IVIM parameter f value facilitated visual differentiation in the knee joint of children with juvenile idiopathic arthritis .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The perfusion information is useful for the assessment of inflamed synovitis in RA because an increased number/area of capillaries is observed in the inflamed synovial membrane as compared with the normal synovial membrane. 19,20 As for differentiating synovitis from joint effusion using perfusion information, Hilbert et al indicated that the IVIM parameter f value facilitated visual differentiation in the knee joint of children with juvenile idiopathic arthritis. 15 However, IVIM parameter f and D* values were not significantly different in the current study when compared between combinations of contrast enhancement grades indicative of synovial proliferation and those indicative of joint effusion.…”
Section: Discussionmentioning
confidence: 99%